Isolation, Expression Profiling, and Regulation via Host Allelochemicals of 16 Glutathione S-Transferases in the Chinese White Pine Beetle, Dendroctonus armandi - Gao, Haiming; Dai, Lulu; Fu, Danyang; Sun, Yaya; Chen, Hui (Frontiers in Physiology, 2020)
The Chinese white pine beetle (Dendroctonus armandi) is undoubtedly one of the most important pests causing ecological damage in the Qinling Mountains. When bark beetles invade conifers, they must overcome host tree defense, including primary resistance and induced resistance responses. Moreover, that's what induced resistance is following herbivory by bark beetles. Bark beetles have a corresponding defense mechanism for degrading toxic compounds, and glutathione S-transferases (GSTs) can catalyze the binding of endogenous substances that reduce glutathione (GSH) to various harmful electrophilic substrates, increasing their solubility and facilitating their excretion from cells. In this experiment, we successfully obtained sixteen full-length sequences of D. armandi, which belonged to four GSTs categories (delta, epsilon, sigma and theta). Transcript levels of sixteen GSTs in D. armandi were compared at four developmental stages (larvae, pupae, teneral adults and adults), three different tissues (antennae, gut and reproductive organs), and under various levels of terpenoid stimuli during feeding on phloem tissue to evaluate the various relevant modes of action. This study aids in the understanding of the interactions between monoterpenes and beetles, and beetles’ detoxification through GSTs.